362 Priming of the Brain Tumor Microenvironment Enables Improved Nanomedicine Delivery. (August 2016) - Chen, Yuanxin; Jiang, Wen; Qie, Yaqing; Liu, Xiujie; von Roemeling, Christina; Shih, Kevin; Wharen, Robert E.; Kim, Betty Y.S.
Abstract : INTRODUCTION: A major challenge in cancer nanotechnology is the efficient delivery of nanomedicines into solid tumors. Nanomedicine relies on a functional vascular network and minimal tissue resistance to achieve homogeneous transport and distribution in solid tumor via convection- and diffusion-based mechanisms. This is especially true for brain tumors, where the presence of specialized blood-brain barrier further impedes transport of nanomedicine from the systemic circulation into the central nervous system. Unlike blood vessels within healthy tissues, tumor vessels are often morphologically pathological and functionally impaired, due to an imbalance of pro- and antiangiogenic growth factor production within the tumor microenvironment. Furthermore, within the tumor stroma, excessive and heterogeneous productions of collagen and other matrix proteins further restrict nanomedicine distribution. METHODS: We characterized in real-time, perfusion and diffusion parameters of luminescent nanoparticles using syngeneic GL261 and the spontaneous RCAS-hPDGFb-HA/nestin Tv-a; Ink4a/Arf−/− brain tumor model with multiphoton imaging in vivo. RESULTS: We demonstrate that tumor vasculature exhibits increased permeability and decreased perfusion capacity compared with normal vessels. As a result, transport of nanomedicine across the vessel wall into the tumor stroma is strongly dependent on particle size and surface polarity. Intratumoral mapping of nanomedicine distribution reveals that once gaining entry into tumors, nanoparticles often experience perivascular clumping and are unable to reach tumor tissue beyond 20 µm from the nearest vessels. Finally, with therapeutic modulation of the tumor microenvironment using anti-VEGFr or anti-TGFβ1 antibody treatments to remodel the tumor vasculature and collagen matrix, respectively, we show that tumors begin to exhibit improved tissue perfusion with improved delivery and distribution with nanomedicine into the tumor interstitium. CONCLUSION: The successful implementation of this combined therapeutic approach can have significant implications in developing effective targeted nanomedicines for brain tumors. These findings suggest that optimized delivery of nanomedicine for brain tumors may be possible through the modulation of both the tumor vasculature and extracellular matrix.